Appreciation and Creation in Ceramic Art Learning as A Form of Cultural Preservation for Students of TK Pandeyan 2 Sukoharjo in Surakarta Residency - Wahyuningsih, Novita; Amboro, Joko Lulut (citeus, 2017)
This study is aimed to describe the process of ceramic art learning process and to determine the impact of ceramic art learning for students of TK Pandeyan 2 Kindegarten of Sukoharjo by appreciating their creations. This method also intended to introduce and preserve ceramic culture for early age students. The method used is qualitative data analysis, in the form of data reduction, data presentation, and conclusion. The result shows that the ceramic art learning in TK Pandeyan 2 Kindegarten of Sukoharjo has positive effects as the teaching and learning process can be used as a medium for teachers and parents to understand children’s characters and personalities better.